Altered microbial P cycling genes drive P availability in soil after afforestation. (15th February 2023) - Zhi, Ruochen; Deng, Jian; Xu, Yuling; Xu, Miaoping; Zhang, Shuohong; Han, Xinhui; Yang, Gaihe; Ren, Chengjie
Abstract: Soil Phosphorous (P) availability is a limiting factor for plant growth and regulates biological metabolism in plantation ecosystems. The effect of variations in soil microbial P cycling potential on the availability of soil P during succession in plantation ecosystems is unclear. In this study, a metagenomics approach was used to explore variations in the composition and diversity of microbial P genes along a 45-year recovery sequence of Robinia pseudoacacia on the Loess Plateau, as well soil properties were measured. Our results showed that the diversity of P cycling genes (inorganic P solubilization and organic P mineralization genes) increased significantly after afforestation, and the community composition showed clear differences. The gcd and ppx genes were dominant in inorganic P transformation, whereas phnM gene dominated the transformation of organic P. The abundance of genes involved in inorganic P solubilization and organic P mineralization was significantly positively correlated with P availability, particularly for phnM, gcd, ppx, and phnI genes, corresponding to the phyla Gemmatimonadetes, Acidobacteria, Bacteroidetes, and Planctomycetes . The critical drivers of the microbial main genes of soil P cycling were available P (AP) and total N (TN) in soil. Overall, these findings highlight afforestation-induced increases in microbial P cycling genes enhanced soil P availability. and help to better understand how microbial growth metabolism caused by vegetation restoration in ecologically fragile areas affects the soil P cycling. Highlights: The diversity of microbes with P cycling genes increased by afforestation. PhnM, gcd, ppx, and phnl genes dominated the increase of soil P availability. The key drivers of the microbial main genes of soil P cycling were AP and TN.